The adoption of technology on construction waste management in Kelantan / Mohamad Hazuan Hazri - Hazri, Mohamad Hazuan (2021)
There is an increase in the problems of environmental sustainability, such as environmental pollution, air pollution, and water pollution impairment arising from construction waste management. Because of the adverse effects of widespread and uncontrolled disposal of construction waste nowadays, which can have a major impact on the environment and its sustainability, the implementation of technology for construction waste management can reduce the environmental pollution problems that can lead to damage and reduce the pollution arising from that act. The barriers to implementing technology for construction waste management in Kelantan, however, are a lack of modern technology, the cost of the technology, and the lack of a strategy for implementing modern technology. Hence, the aim of this research is to suggest proper solutions to enhance the effectiveness of waste management systems in the construction industry. Surveys were used to collect data for this paper, and questionnaires were distributed to contractors, project managers, architects, and engineers. The outcome of this research will include several capabilities of modern technology that could be applied, challenges in terms of cost and the strategies to implement the technology for construction waste management. It is important to develop and implement technology in Kelantan soon and toward sustainability.